2006
DOI: 10.1007/s00276-006-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

The membranous layer of superficial fascia: evidence for its widespread distribution in the body

Abstract: A discrete membranous layer, "stratum membranosum", in human subcutaneous tissue is classically described as confined to the lower anterior abdominal wall and perineum and referred to as Scarpa's and Colles' fasciae, respectively. Evidence for its existence elsewhere in the body is scanty and therefore the present study was undertaken. Dissection of six embalmed adult cadavers, along with ultrasound imaging on four living subjects, were carried out to determine the existence, topography, and thickness of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 17 publications
3
84
1
1
Order By: Relevance
“…Markman and Barton studied the anatomy of the subcutaneous fat tissue in the trunk and extremities and confirmed the presence of a membranous layer in the thigh 44 . Others noted that the anatomy of the membranous layer varied with sex, adiposity, and body region 45 and that it was thicker in the lower compared with the upper extremity and on the posterior compared with the anterior aspect of the body 46 . Many anatomical studies have described the LFCN anatomy and its variations in relation to the ASIS, the approach for iliac crest bone harvesting, or the surgical management of meralgia paresthetica [19][20][21][22][23][24][25][26]40 .…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
“…Markman and Barton studied the anatomy of the subcutaneous fat tissue in the trunk and extremities and confirmed the presence of a membranous layer in the thigh 44 . Others noted that the anatomy of the membranous layer varied with sex, adiposity, and body region 45 and that it was thicker in the lower compared with the upper extremity and on the posterior compared with the anterior aspect of the body 46 . Many anatomical studies have described the LFCN anatomy and its variations in relation to the ASIS, the approach for iliac crest bone harvesting, or the surgical management of meralgia paresthetica [19][20][21][22][23][24][25][26]40 .…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I mentioning
confidence: 99%
“…3) In mild edema, a thin EFS is seen along with horizontally or obliquely oriented echogenic lines, i.e., the superficial fascia, in which collagen fibers are running in all directions. Since most of the superficial nerves, arteries, veins, and lymphatics are embedded in this layer, 6) initial accumulation of fluid in this space may be reasonable. The EFS in the sub-dermal area or above the deep (muscular) fascia may be seen in earlier stages of edema, both of which are again horizontally oriented.…”
Section: Subcutaneous Echogenicitymentioning
confidence: 99%
“…The primary function of the superficial fascia is to encase, support, and shape the fat of certain body regions and to hold the skin onto the underlying tissue. 6) Since it has been reported that the amount and thickness of superficial fascia varies in different parts of the body, 6,10) it is estimated that the compliance of the subcutaneous tissue may be different in the medial and lateral lower leg.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Although the structure of subcutaneous tissue differs between various regions of the human body, common components have been identified in several anatomical parts. The existence of a generic pattern of organization of the SSC was put forward several years ago [11], then confirmed in recent radiological work [1] at the level of the arms, legs and trunk. Nevertheless, this anatomical finding has never been the basis of a generic modeling of the human SSC.…”
Section: Introductionmentioning
confidence: 82%